Urethral Stricture and Methods for its Correction - R. А. Kazikhinurov; B. I. Shamsov; A. A. Kazikhinurov; R. R. Kazikhinurov; A. I. Hasanov (Креативная хирургия и онкология, 2023)
A stricture is a type of narrowing of the urethra, which can be caused by a variety of reasons. In addition, urethral strictures are associated with a wide range of symptoms and require special diagnostic examination before proceeding with any treatment. The treatment of urethral strictures has remained a challenge for many years. Stricture recurrence is still a serious problem in reconstructive urology. During the second half of the 20th century, urologists tried to find solutions for treating both simple and complex urethral strictures. Within the last few decades research has mainly focused on improving existing procedures to mitigate the negative postoperative effects. Despite considerable scientific achievements in this area, numerous studies have revealed a lack of knowledge about urethral stricture surgery among urologists and have shown that patients with urethral strictures are generally offered inadequate treatment options. Currently, many surgical interventions are available to treat this condition. However, the variety of treatment methods reflects a lack of optimal technique. This bibliographical review presents data on the effectiveness of minimally invasive (endoscopic) and various urethroplasty options in urological practice.